2013
DOI: 10.1134/s1547477113070169
|View full text |Cite
|
Sign up to set email alerts
|

Pion dissociation and Levinson’s theorem in hot PNJL quark matter

Abstract: Pion dissociation by the Mott effect in quark plasma is described within the generalized Beth-Uhlenbeck approach on the basis of the PNJL model which allows for a unified description of bound, resonant and scattering states. As a first approximation, we utilize the Breit-Wigner ansatz for the spectral function and clarify its relation to the complex mass pole solution of the pion Bethe-Salpeter equation. Application of the Levinson theorem proves that describing the pion Mott dissociation solely by means of sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 24 publications
2
51
0
Order By: Relevance
“…Future studies should acknowledge that, after the Mott transition, are the two-body scattering states, rather than the resonances who play a crucial role [60]. Bearing in mind the technical difficulties encountered within the present approach, we may speculate that one possible way to proceed while still keeping the covariant setup, would be to put forward the picture of complexconjugate singularities in a Gribov-Zwanziger framework, where they would be seen as elementary fields.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Future studies should acknowledge that, after the Mott transition, are the two-body scattering states, rather than the resonances who play a crucial role [60]. Bearing in mind the technical difficulties encountered within the present approach, we may speculate that one possible way to proceed while still keeping the covariant setup, would be to put forward the picture of complexconjugate singularities in a Gribov-Zwanziger framework, where they would be seen as elementary fields.…”
Section: Discussionmentioning
confidence: 96%
“…Masses and widths can be extracted which encode information on the medium modification of mesons by the underlying quark-antiquark substructure. Therefore, the nl-PNJL, and quark (and gluon) models in general, are in an interesting position to properly account for the degrees of freedom in both, the hadron and the QGP phases, with the underlying physical mechanism for the vanishing of hadronic states from the spectrum in the QGP phase being their dissolution in the continuum of scattering states (the Mott effect) [55][56][57][58][59][60][61][62].…”
Section: Introductionmentioning
confidence: 99%
“…Our work might be considered as a first step towards a microscopically based construction of the transition from hadron to quark matter either via pasta phases or beyond mean-field studies taking into account the quark substructure of hadrons and their dissociation in the dense medium [21,22]. …”
Section: Discussionmentioning
confidence: 99%
“…Recently, invoking the Levinson's theorem, it has been shown that keeping only the bound-state spectrum in thermodynamical computations leads to strong violations of unitarity [39]. In our calculations, we take into account the continuum as well the bound states, in order to keep unitarity.…”
Section: Solving Lippman-schwinger Equationsmentioning
confidence: 99%